(3QSGdI aj GdJLhjOs - (3GdMSfj GdMSjfj GdYGedj, GdYGedj, LhGO (B((3Ch eMeO LhGO(B) (3Hf eMeO Hf eMeO GdMSfj GdMSjfj, J (B1226(3g` (B1811(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3agPG eG SFdJehg eeG dG jSY CMO Cf jLgdg hdG HO def bQC Ch PcQ hGLHG Cf jYdeg dCf YdeGFfG bO TOOhG ZGjI GdJTOjO Ydi GdeMGaXI Ydi GdJTOjO hGdGOZGe GdUZjQs
(3BNQgG (B:s
(3BNQgG(B: (3hcdgG EPG hbYJ HYO GdQGA dCfg jTHg MQa GdGSJYdGA dCfgG JNQL ef WQa GddSGf hWdA jdjg aj GdMfc GdCYdi GdPj gh eMd MQa GdGSJYdGA(B. (3hGdMeO ddg hMOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 143s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs